Food Preparation and Cooking Levels 1 and 2 - Hayter, Roy (Australia : Thomson Learning Asia, 2000)
This comprehensive resource has been completely updated for the NVQ/SVQ level 1 and 2 Food Preparation and Cooking units. Roy Hayter covers the basic skills and underpinning knowledge for the 10 level 1 and 19 level 2 cookery units.
Introducing food preparation and cooking -- Safety, security and personal hygiene in food preparation and cooking -- Hygiene in food storage, preparation and cooking -- Maintaining and handling knives -- Food handling and storage -- Cleaning food production areas, equipment and utensils -- Working in food preparation and cooking -- Preparing and cooking basic meat, poultry and offal dishes -- Preparing and cooking basic fish dishes -- Preparing and cooking basic sauces and soups -- Preparing and cooking basic vegetable dishes and salads -- Preparing and cooking basic vegetable protein dishes -- Preparing and cooking basic pulse dishes -- Preparing and cooking basic rice dishes -- Preparing and cooking basic pasta dishes.
Includes index.
Keywords: COOKBOOKS